The Causes of Low Learning Achievement of Sharia Accounting Subject Among Sharia Economics Students - Dwiya Endah Pandu Probowati; Anis Chariri; Jaka Isgiyarta (Dinamika Pendidikan, 2023)
The purpose of this research is to find empirical evidence that causes low learning achievements in sharia accounting subject on sharia economics students. This study uses a qualitative interpretive case study method to explore and reveal information that cannot be explained by other research methods, as well as conducting causal investigations related to an event being studied. The research findings are there is an internal and external factor that caused the low learning achievement on sharia accounting subjects. The internal factors within the students include: First, the lack of basic knowledge of introductory accounting. Second, The low interest and motivation in subjects that use mathematical calculations. Third, No motivation to study the supporter subjects (introductory accounting fiqh muamalah) independently. The external factors that caused the low learning achievement among sharia economics students are: First, the learning duration in the class room, Second, the existing curriculum does not accommodate the success of learning achievement. Third, the learning environment is not conducive.